Ekstraksi Informasi Destinasi Wisata Populer Jawa Timur Menggunakan Depth-First Crawling - Sepyan Purnama Kristanto; Lutfi Hakim (Universitas Bumigora, 2021)
Travel Destinations are an inseparable part of human life today. As one of the provinces with a large area, East Java is one of the most visited areas for its tourism. Many people are competing in finding information related to these tourist destinations on the internet, one of which is the Tripadvisor application. Of the many tourist attractions, several tourist attractions have different attractions and experiences each time. Tourists have widely used the Tripadvisor application in determining the location where they will visit on their vacation activities. With various features ranging from reviews and recommendations for sharing photos, TripAdvisor is one of the best applications in the inventory of tourist attractions. Of the many tourist destinations, it is necessary to analyze and evaluate both tourist attractions that have many visitors with tourist attractions that are rarely visited by both local and foreign visitors. This goal, information mining (web mining), was carried out on the TripAdvisor application to obtain information on East Java Province's popular destinations. Crawling results on the TripAdvisor website, obtained various kinds of information such as names of tourist attractions, locations, visitor reviews, photos, and ratings of these tourist attractions. Spatial Analysis, a Tourist Sentiment Analyst on tourist objects, can then be carried out. It can also be developed into the recommendation system for the best tourist attractions in East Java Province